2006
DOI: 10.1016/j.ydbio.2005.12.037
|View full text |Cite
|
Sign up to set email alerts
|

Mxi1 is essential for neurogenesis in Xenopus and acts by bridging the pan-neural and proneural genes

Abstract: We have isolated and characterized Xenopus Mxi1, a member of the Myc/Max/Mad family of bHLHZip transcription factors. Xmxi1 transcripts are present during gastrulation and early neurula stages, earlier and in broader domains as compared to the neuronal determination factor neurogenin (X-ngnr-1). Consistent with an early role in neurogenesis, Xmxi1 is positively regulated by Sox3, SoxD, and proneural genes, as well as negatively by the Notch pathway. Loss-of-function experiments demonstrate an essential role fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
16
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 75 publications
1
16
1
Order By: Relevance
“…However, the studies described here support the conclusion that Mad3 promotes proliferation in cultured GNPs and appears to have overlapping activity with Nmyc. The only previous report indicating a functional role of a Mad family member in processes related to proliferation is a recent study suggesting that Xenopus Mxi1 (Xmxi1) is essential for neurogenesis during embryogenesis (27). However, this study demonstrated that Xmxi1 plays an important role in the formation of the mature neural fate, which is necessary for activation by factors that induce neuronal differentiation, and this activity is not directly related to an active role in cell cycle progression.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…However, the studies described here support the conclusion that Mad3 promotes proliferation in cultured GNPs and appears to have overlapping activity with Nmyc. The only previous report indicating a functional role of a Mad family member in processes related to proliferation is a recent study suggesting that Xenopus Mxi1 (Xmxi1) is essential for neurogenesis during embryogenesis (27). However, this study demonstrated that Xmxi1 plays an important role in the formation of the mature neural fate, which is necessary for activation by factors that induce neuronal differentiation, and this activity is not directly related to an active role in cell cycle progression.…”
Section: Discussioncontrasting
confidence: 55%
“…Indeed, the original Mad3 cloning and characterization study demonstrated that overexpression of Mad3 (like that of Mad1) is capable of inhibiting Myc-dependent transformation of rat embryo fibroblasts (22), supporting the model that Mad proteins antagonize Myc function in cell growth and VOL. 27,2007 Mad3 REGULATES GRANULE CELL PROLIFERATION 8185…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mxi1 also contains an N-terminal Sin3-interacting domain, which recruits the general co-repressor protein Sin3 and an associated transcriptional repression complex containing histone deacetylases to the transcription regulatory regions of target genes. As a result, the core histones are deacetylated and the transcription of target genes is suppressed [14].Some investigators have shown that Mxi1 inhibits the proliferation of DU145 human prostate cancer cells and U87 glioma cells [11,15]. Mutations and deletions in the Mxi1 coding sequence have been described in patients with prostate cancer, neurofibrosarcoma, and neuroglioma [16,17].In addition, Mxi1-knockout mice exhibit a tumorigenic phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…The neuronal determination factor X-ngnr-1 robustly induced the activation of both CRMP-4 and CRMP-2. The positive regulation of CRMP-2 by X-ngnr-1 is similar to the activation of other panneural genes such as Nrp-1 and NCAM (Klisch et al, 2006). …”
mentioning
confidence: 76%